The political economy of priority-setting for health in South Sudan: a case study of the health pooled fund - Heloise Widdig; Noor Tromp; George William Lutwama; Eelco Jacobs (BMC, 2022)
Abstract Background In fragile and conflict affected settings (FCAS) such as South Sudan, where health needs are immense, resources are scarce, health infrastructure is rudimentary or damaged, and government stewardship is weak, adequate health intervention priority-setting is especially important. There is a scarcity of research examining priority-setting in FCAS and the related political economy. Yet, capturing these dynamics is important to develop context-specific guidance for priority-setting. The objective of this study is to analyze the priority-setting practices in the Health Pooled Fund (HPF), a multi-donor fund that supports service delivery in South Sudan, using a political economy perspective. Methods A multi-method study was conducted combining document review, 30 stakeholder interviews, and an examination of service delivery. An adapted version of the Walt and Gilson policy analysis triangle guided the study's design and analysis. Results Priority-setting in HPF occurs in a context of immense fragility where health needs are vast, service delivery remains weak, and external funding is essential. HPF's service package gives priority to the health of mothers and children, gender-sensitive programming, immunization services, and a community health initiative. HPF is structured by a web of actors at national and local levels with pronounced power asymmetries and differing vested interests and ideas about HPF's role. Priority-setting takes place throughout program design, implementing partner (IP) contract negotiation, and implementation of the service package. In practice the BPHNS does not provide adequate guidance for priority-setting because it is too expansive and unrealistic given financial and health system constraints. At the local level, IPs must manage the competing interests of the HPF program and local health authorities as well as challenging contextual factors, including conflict and shortages of qualified health workers, which affect service provision. The resulting priority-setting process remains implicit, scarcely documented, and primarily driven by donors' interests. Conclusion This study highlights power asymmetries between donors and national health authorities within a FCAS context, which drive a priority-setting process that is dominated by donor agendas and leave little room for government ownership. These findings emphasize the importance of paying attention to the influence of stakeholders and their interests on the priority-setting process in FCAS.